Corak Baru Pelacakan Hadis Pada Era Digital Berbasis Maktabah Al-Syamilah - Babun Najib; Budi Ichwayudi; Fahrur Razi; Muhid (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The rapid development of information technology in recent times, particularly in the realm of digitization, closely aligns with the progress of human civilization. This trend is primarily propelled by the demands for efficiency and effectiveness in accessing information. The societal need for information access, particularly concerning the tracking of hadiths as a fundamental source in Islam, further accelerates the evolution of this technology. Hence, the implementation of various information technology features, such as those available in the Maktabah al-Syamilah application, becomes crucial. This study adopts a case study approach, with a research focus centered on the Maktabah al-Syamilah application as the research material object. The objective of this research is to operate various features within the application, aiming to enhance the effectiveness of hadith tracking. The research findings indicate that the Maktabah al- Syamilah application was designed with the purpose of digitizing Islamic book information by Nafi and was first introduced in 2016. The application facilitates hadith tracking with straightforward steps. In addition to contributing to the development of hadith tracking techniques (takhrij hadith) formulated by previous scholars, this application also plays a significant role in digitizing hadiths that were previously challenging for many individuals to access.